2006
DOI: 10.1136/gut.2006.091322
|View full text |Cite
|
Sign up to set email alerts
|

The role of the sympathetic nervous system in intestinal inflammation

Abstract: The nervous system in the intestine controls motility, secretion, sensory perception, and immune function. Peptidergic neurones with neurotransmitters such as substance P and nerve growth factors have been the main focus of neuroimmunomodulation research in the gut. This review summarises the present knowledge concerning the role of the sympathetic nervous system (SNS) in modulating intestinal inflammation. The role of the SNS for gut inflammation is compared with its role in rheumatoid arthritis which demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
143
0
6

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(154 citation statements)
references
References 101 publications
5
143
0
6
Order By: Relevance
“…Cortisol, through a feedback loop, regulates the levels of CRF and ACTH. Importantly, immune cells, through the COX-2 pathway and production of PEG-2 during (pro-) inflammation, stimulate the adrenal gland to produce cortisol, which supports the β adrenergic pathway in its anti-inflammatory effect (Straub et al, 2006). This indicates that under normal conditions the neuroendocrine and immune systems coordinate to maintain homeostasis.…”
Section: Microbiota and Humoral Responsesmentioning
confidence: 99%
“…Cortisol, through a feedback loop, regulates the levels of CRF and ACTH. Importantly, immune cells, through the COX-2 pathway and production of PEG-2 during (pro-) inflammation, stimulate the adrenal gland to produce cortisol, which supports the β adrenergic pathway in its anti-inflammatory effect (Straub et al, 2006). This indicates that under normal conditions the neuroendocrine and immune systems coordinate to maintain homeostasis.…”
Section: Microbiota and Humoral Responsesmentioning
confidence: 99%
“…There is an increase in endogenous cortisol, adrenaline, noradrenaline and adenosine. Investigations by Straub et al [20] showed this effect on acute inflammatory reactions. When inflammation persists over a longer period, such as in rheumatoid arthritis, it seems to come to a kind of adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…Straub et al [20] have shown that, number of sympathetic nerve fibers is reduced in synovial fluid of rheumatic joints [20]. In the immediate environment of an inflammatory process, sensory nerve fibers are stimulated, and the hypothalamus-pituitary axis also stimulates the sympathetic nervous system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall effect of the sympathetic innervation of the GI tract is a reduction in activity achieved by lowering epithelial electrolyte secretion, blood flow, and gut motility (Lomax et al 2010). There is also evidence that the SNS interacts with the immune system to modulate GI inflammation (McCafferty et al 1997;Straub et al 2008;Straub et al 2006) by actions on cells of the innate and adaptive immune systems (Elenkov et al 2000;Sanders 2012). …”
Section: Structure and Function Of The Sympathetic Innervation Of Thementioning
confidence: 99%